Business Model Canvas (BMC) Training to Support the Strengthening of Student Entrepreneurship - Widyastuti, Umi; Maulida, Ervina; Yuniarti, Puji; Lestari, Fitra Dila; Gurendrawati, Etty; Dara, Despinur; Ulupui, IGKA (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2024)
The Indonesian government prioritizes policies aimed at fostering entrepreneurship across all segments of society. This initiative aims to promote the attainment of the sustainability development goals (SDGs), which have been introduced through various initiatives and are projected to be accomplished between 2015 and 2030. Entrepreneurship remains a less favored means of earning a living among certain Indonesians. Particularly among the youth, there is a prevalent belief that pursuing entrepreneurship is not their primary ambition or aim. The correlation between entrepreneurship and economic growth has been well-established. Consequently, studying entrepreneurship education becomes a compelling endeavor to foster entrepreneurship, particularly among aspiring entrepreneurs. The business model canvas (BMC), enables users to synchronize earnings with objectives, including environmental and social dimensions. The purpose of this training exercise was to establish the following objectives aree to enhance comprehension and effectively employ the Business Model Canvas (BMC) in the process of business planning, to enhance proficiency in creating BMC as a means of managing business plans and to promote the adoption of BMC as a solution to the business planning challenges faced by entrepreneurial students. The implementation of community service (PkM) aims to foster international collaboration between lecturers and students from UNJ and UMS. It is expected to enhance understanding, knowledge, and make a constructive impact on the business planning and development of BMC with the business community.